Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/jhep02(2014)033
|View full text |Cite
|
Sign up to set email alerts
|

Volume law for the entanglement entropy in non-local QFTs

Abstract: In this paper, we present a simple class of non-local field theories whose ground state entanglement entropy follows a volume law as long as the size of subsystem is smaller than a certain scale. We will confirm this volume law both from numerical calculations and from analytical estimation. This behavior fits nicely with holographic results for spacetimes whose curvatures are much smaller than AdS spaces such as those in the flat spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 61 publications
4
74
0
Order By: Relevance
“…There is a difference between these solutions and the ones we have discussed so far, in that these solutions no longer follow the standard Area Law but instead follow a "Volume Law" for the divergent part of the EE. This observation was also made in other contexts by [35][36][37]. From this insight we can try to understand in which cases these new Volume Law solutions may be relevant to our question.…”
Section: Jhep06(2014)005supporting
confidence: 61%
“…There is a difference between these solutions and the ones we have discussed so far, in that these solutions no longer follow the standard Area Law but instead follow a "Volume Law" for the divergent part of the EE. This observation was also made in other contexts by [35][36][37]. From this insight we can try to understand in which cases these new Volume Law solutions may be relevant to our question.…”
Section: Jhep06(2014)005supporting
confidence: 61%
“…7 The model of our interest for large dynamical JHEP07(2017)120 exponents is similar to a certain non-local scalar theory studied in [40]. In figure 4 we have shown that this scaling behavior also happens for Renyi entropies for large values of z.…”
Section: Review Of Correlator Methodsmentioning
confidence: 58%
“…Volume law scaling of entanglement entropy has been previously observed in several field theories with nonlocal effects [40][41][42][43][44] (See also [45] for a perturbative study of entanglement entropy in nonlocal theories.). 7 The model of our interest for large dynamical JHEP07(2017)120 exponents is similar to a certain non-local scalar theory studied in [40].…”
Section: Review Of Correlator Methodsmentioning
confidence: 84%
“…In string theory examples of AdS/CFT, a gravity dual usually includes an internal compact space in addition to the AdS spacetime, as is typical in the AdS 5 × S 5 type IIB string background dual to the four dimensional N = 4 super Yang-Mills. Therefore one may wonder how quantum entanglement in CFTs can probe internal spaces such as S 5 . As we will discuss in the final part of this paper, this question is closely related to the entanglement entropy between two interacting CFTs (1.3).…”
Section: Jhep04(2014)185mentioning
confidence: 99%
“…For example, this quantity follows the area law [1][2][3][4] if we consider a local quantum field theory with a UV fixed point, while non-local field theories [5,6] or QFTs with fermi surfaces [7,8] at UV cut off scale can violate the area law. Moreover, the coefficients of logarithmically divergent terms of S A in even dimensional conformal field theories (CFTs) are proportional to central charges [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%